Utilization Of Audio-Visual Teaching Materials In Learning Sharaf - Moh Akbar Muzakki; R Taufiqurrahman; Nur Ila Ifawati (Nurul Jadid University, 2025)
The rapid development of digital technology has transformed traditional Arabic learning into a more interactive and student-centered process. This study aims to analyze the use of audiovisual teaching materials in Sharaf (Arabic morphology) instruction and their impact on students’ cognitive engagement and comprehension. Using a qualitative case study design, data were collected through interviews, observations, and document analysis in Arabic language classes implementing digital media integration. The findings reveal that animated morphology charts, narrated videos, and interactive slides effectively enhance students’ retention, recall accuracy, and motivation. Moreover, multisensory engagement through synchronized visual and auditory input supports a more profound understanding of morphological transformations. The study contributes to digital Arabic pedagogy by presenting a model of sustainable, multimodal instruction. It recommends continued development of context-based audio-visual materials to strengthen learner autonomy and ensure long-term pedagogical innovation in Arabic linguistic education.